Pengaruh Pengetahuan Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi dengan Kesadaran Wajib Pajak sebagai Variabel Mediasi - Mita Melinda; Eko Wahjudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Taxes are mandatory contributions for citizens that are given to the state without receiving direct compensation and are used by the government for the prosperity of the people. One type of tax is income tax. To increase taxpayer compliance, taxpayers must have high tax knowledge and awareness. This research aims to examine the influence of tax knowledge on taxpayer compliance, tax knowledge on taxpayer awareness, taxpayer awareness of taxpayer compliance, and taxpayer awareness is able to mediate the influence of taxpayer knowledge on taxpayer compliance. This research used a sample of 95 respondents with Structural Equation Model (SEM) analysis. The results of the research show that tax knowledge has no effect on taxpayer compliance, tax knowledge has an effect on taxpayer awareness, taxpayer awareness has an effect on taxpayer compliance, and taxpayer awareness is able to mediate the effect of tax knowledge on taxpayer compliance.